Doxycycline Suppresses Hypertension through Renin– Angiotensin System (RAS) Regulation: Insights from Molecular Docking and Renal Gene Expression - Ariski Fajarido; Fadilah Fadilah; Wawaimuli Arozal; Jaka Fajar Fatriansyah; Agrin Febrian Pradana; Edwina Rugayah Monayo (Cell and BioPharmaceutical Institute, 2026)
Background: Doxycycline, a tetracycline antibiotic known for inhibiting matrix metalloproteinases, has shown potential antihypertensive effects. However, its role in modulating the renin–angiotensin system remains poorly understood. This study aims to specifically evaluate Doxycycline’s effects on key RAS components and blood pressure responses to clarify its underlying mechanism and support its development as a targeted antihypertensive therapeutic candidate.Materials and Methods: This study integrated an in-silico and experimental approach to assess the antihypertensive effects of doxycycline. Bioinformatics analyses were first conducted, including target prediction, gene ontology enrichment, hub-gene identification, PPI network construction, and KEGG pathway analysis, followed by molecular docking and molecular dynamics simulations to predict doxycycline’s interactions with key RAS targets. To validate these computational findings, qRT-PCR was performed to measure the expression of selected genes in kidney tissues from hypertensive rats.Results: Bioinformatics analysis identified six key target genes, including AGT, AGTR1, AGTR2, REN, ACE, and ACE2. Molecular docking showed that doxycycline exhibited stronger binding affinity to AGTR1 (-8.346 kcal/mol) than its native ligand. Molecular dynamics confirmed the stability of the doxycycline–AGTR1 complex at 20 ns. Gene expression analysis of kidney tissues from hypertensive rats revealed a significant reduction in AGTR1 expression in the group treated with doxycycline 15 mg/kg (p<0.05), while no significant change was observed at 30 mg/kg.Conclusion: Low-dose doxycycline may modulate the renin–angiotensin pathway through AGTR1 inhibition, indicating its potential as a candidate for further antihypertensive research and warranting more comprehensive in vivo evaluation.Keywords: Hypertension, doxycycline, molecular docking, gene expression, Renin-Angiotensin System